2019
DOI: 10.1016/j.physbeh.2019.112618
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of insulin action during single soccer sessions before and after a 12-week training period in type 2 diabetes patients on a caloric-restricted diet

Abstract: Biomarkers of insulin action during single soccer sessions before and after a 12-week training period in type 2 diabetes patients on a caloric-restricted diet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 41 publications
4
20
0
1
Order By: Relevance
“…During a 1-hour football training session in 21 middle-aged males with type 2 diabetes, the distance covered was 4.7 ± 0.2 km and mean heart rate was 83 ± 2 % of maximal heart rate, corresponding a blood lactate increase from 2.1 ± 0.3 to 8.2 ± 1.3 mmol/L [13]. In line with this, a 40-min supervised recreational football training in 51 middle-aged patients with type 2 diabetes induced increases in blood lactate from 1.4 ± 0.1 to 6.0 ± 0.7 mmol/L as well as in glucagon levels from 112.1 ± 6.2 ± 142.9 ± 8.0 pg/mL, whereas glucose and insulin levels remained unchanged [14].…”
Section: Reviewsupporting
confidence: 71%
See 2 more Smart Citations
“…During a 1-hour football training session in 21 middle-aged males with type 2 diabetes, the distance covered was 4.7 ± 0.2 km and mean heart rate was 83 ± 2 % of maximal heart rate, corresponding a blood lactate increase from 2.1 ± 0.3 to 8.2 ± 1.3 mmol/L [13]. In line with this, a 40-min supervised recreational football training in 51 middle-aged patients with type 2 diabetes induced increases in blood lactate from 1.4 ± 0.1 to 6.0 ± 0.7 mmol/L as well as in glucagon levels from 112.1 ± 6.2 ± 142.9 ± 8.0 pg/mL, whereas glucose and insulin levels remained unchanged [14].…”
Section: Reviewsupporting
confidence: 71%
“…During traditional football training intervention, information with regard to orthopaedic complaints was available only in one study. In 51 males with type 2 diabetes receiving 40-minute football training sessions three times per week for 12 weeks, no one received an injury [14], indicating that recreational football is a safe sport in diabetes patients. Football combines elements of HIIT, endurance training and strength training, thereby providing optimal stimuli for osteogenic and musculoskeletal fitness.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 included studies were published from 1987 to 2019, including three RCTs (Baum et al, 2007;Eriksen et al, 2007;de Sousa et al, 2019), three NRCTs (Opitz et al, 2014a(Opitz et al, , 2015Støa et al, 2017), and seven case-control studies (Schneider et al, 1987;Dela et al, 1995;Holton et al, 2003;Juel et al, 2004;Michishita et al, 2008;Mogensen et al, 2009;Scheede-Bergdahl et al, 2014). Three studies (Mogensen et al, 2009;Opitz et al, 2015;Støa et al, 2017) were assessed as "good" quality, nine studies (Schneider et al, 1987;Dela et al, 1995;Holton et al, 2003;Juel et al, 2004;Baum et al, 2007;Eriksen et al, 2007;Michishita et al, 2008;Opitz et al, 2014a;de Sousa et al, 2019) were of "fair" quality, and one study (Scheede-Bergdahl et al, 2014) was rated with "poor" quality. The detailed quality assessment of studies can be found in Supplementary Table 4.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Die akuten Effekte nach einer einzelnen Trainingseinheit sowie die chronischen Effekte nach einem längerfristigen angeleiteten Fußballtraining sind an anderer Stelle im Detail dargestellt [10]. Eine Untersuchung an 51 T2D-Patienten im mittleren Alter von 61 Jahren ergab eine sehr hohe Adhärenz [11]. Die 3-mal pro Woche über 12 Wochen angebotenen 40-minütigen Trainingseinheiten wurden zu 100 % wahrgenommen, ohne dass es zu Verletzungen kam.…”
Section: Reviewunclassified